2017
DOI: 10.1590/1678-992x-2015-0479
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetics theory for genomic selection and efficiency of genotypic value prediction in open-pollinated populations

Abstract: Quantitative genetics theory for genomic selection has mainly focused on additive effects. This study presents quantitative genetics theory applied to genomic selection aiming to prove that prediction of genotypic value based on thousands of single nucleotide polymorphisms (SNPs) depends on linkage disequilibrium (LD) between markers and QTLs, assuming dominance and epistasis. Based on simulated data, we provided information on dominance and genotypic value prediction accuracy, assuming mass selection in an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Several studies have reported that the accuracy of genomic prediction obtained with these methods is higher than with genetic evaluation using pedigree-based BLUP [ 16 18 ]. However, the accuracy obtained from genomic information depends on several parameters including reference population size [ 19 , 20 ], extent of linkage disequilibrium (LD), heritability of the trait [ 20 , 21 ], relationship between training and validation populations [ 10 ] and the genetic architecture of the trait, which relates to the relative size of allele substitution effects at quantitative trait loci (QTL) [ 10 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the accuracy of genomic prediction obtained with these methods is higher than with genetic evaluation using pedigree-based BLUP [ 16 18 ]. However, the accuracy obtained from genomic information depends on several parameters including reference population size [ 19 , 20 ], extent of linkage disequilibrium (LD), heritability of the trait [ 20 , 21 ], relationship between training and validation populations [ 10 ] and the genetic architecture of the trait, which relates to the relative size of allele substitution effects at quantitative trait loci (QTL) [ 10 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of epistasis in studies of quantitative traits in plants [32,33,34,35,36,37], explicit (in the model) or implicit (in hidden layers) inclusion of epistatic interactions may increase the accuracy of prediction [38]. Furthermore, the frequency variation of the epistatic allele between populations may cause the gene-of-interest effect to be significant in one population but not in another, and the effect may even be inverse on the character in different environments [5], which reinforces the importance of using computational intelligence methods that easily incorporate interactions between linear effects through their hidden layers.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP and QTL genotypic data for DH lines, the QTL genotypic data of single crosses, and the phenotypic data for DH lines and single crosses were simulated using the software REALbreeding. The program has been developed by the first author using the software REALbasic 2009 (Viana et al 2017a;Viana et al 2017b;Viana et al 2016;Azevedo et al 2015;Viana et al 2013). Based on our input, the software distributed 10,000 SNPs and 400 QTLs in ten chromosomes (1,000 SNPs and 40 QTLs by chromosome).…”
Section: Simulationmentioning
confidence: 99%